Salon des Refusés : Progetti di public art mai realizzati = Public art projects never realized. - Alves, Maria Thereza; Cuevas, Minerva; Garaicoa, Carlos; Garutti, Alberto; Geers, Kendell; Marisaldi, Eva; Morton, Callum; Orta, Jorge; Orta, Lucy; Pinto, Roberto; Solakov, Nedko; Theis, Bert; et al. (Venezia : Fondazione Bevilacqua La Masa Venezia, 2003)
Alves, Maria Thereza ; Cuevas, Minerva ; Garaicoa, Carlos ; Garutti, Alberto ; Geers, Kendell ; Marisaldi, Eva ; Morton, Callum ; Muntadas, Antoni ; Orta, Jorge ; Orta, Lucy ; Solakov, Nedko ; Theis, Bert ; Xhafa, Sislej
Engels
Italiaans
boek